Surface roughness improvement using volumetric error control through adaptive slicing. (2017) - Taufik, Mohammad; Jain, Prashant K.
This research presents the development of advanced adaptive slicing procedure to improve the surface roughness by adaptively selecting the layer thickness based on the user specified volumetric error (VE) value bound. However, most of the researchers have developed slicing procedures to improve the part surface quality under cusp height concept. Moreover, cusp height-based adaptive slicing procedures do not have any direct control on VE. It is possible that with very little variation in cusp height the large variation in VE may occur on shallow surfaces. In contrast, the advanced adaptive slicing algorithm has been developed and implemented to vary layer thickness directly under a specified VE value on the fused deposition modelling (FDM) part surfaces although this procedure can also be useful for all AM processes to control VE. In this work, different models have been used to estimate VE and surface roughness according to the layer thickness changes.